FTY720 Attenuates LPS-Induced Inflammatory Bone Loss by Inhibiting Osteoclastogenesis via the NF-κB and HDAC4/ATF Pathways - Chongwei Chen; Sujing Zong; Zhenyu Wang; Ruijia Yang; Yanjing Guo; Yunfei Wang; Xinping Chen; Yue Li; Shaowei Wang (Journal of Immunology Research)
Osteoclast (OC) abnormalities lead to many osteolytic diseases, such as osteoporosis, inflammatory bone erosion, and tumor-induced osteolysis. Exploring effective strategies to remediate OCs dysregulation is essential. FTY720, also known as fingolimod, has been approved for the treatment of multiple sclerosis and has anti-inflammatory and immunosuppressive effects. Here, we found that FTY720 inhibited osteoclastogenesis and OC function by inhibiting nuclear factor kappa-B (NF-κB) signaling. Interestingly, we also found that FTY720 inhibited osteoclastogenesis by upregulating histone deacetylase 4 (HDAC4) expression levels and downregulating activating transcription factor 4 (ATF4) expression levels. In vivo, FTY720 treatment prevented lipopolysaccharide- (LPS-) induced calvarial osteolysis and significantly reduced the number of tartrate-resistant acid phosphatase- (TRAP-) positive OCs. Taken together, these results demonstrate that FTY720 can inhibit osteoclastogenesis and ameliorate inflammation-induced bone loss. Which may provide evidence of a new therapeutic target for skeletal diseases caused by OC abnormalities.